Cystoscopic Biopsies of Bladder Neoplasms: A Snippet in Diagnosis - K, Rajeshwari; N, Karibasappa G; Dravid, N V; Patil, Ashish (Annals of Pathology and Laboratory Medicine, 2019)
Introduction: Urinary bladder neoplasms constitute an important source of clinical signs and symptoms which are more disabling than lethal. The present study aimed to study the prevalence of bladder neoplasms and to study the clinico-histomorphological features of various bladder neoplasms along with special emphasis on grading and staging of the bladder tumours. Materials and methods: The present study is a five years retrospective study. All patients who visited to urology outpatient department with lower urinary tract symptoms and obstructive bladder symptoms were subjected to cystoscopy. The detailed clinico-histomorphological features of cystoscopic biopsies are studied using WHO/ISUP 2004 histological grading and TNM staging were used in classifying the bladder tumours. Results: Out of 239 cystoscopic biopsies, the neoplastic lesions constituted 76.6% of the cases Among the neoplastic, benign lesions accounted for 12.9% of the cases and malignant lesions accounted for 83 % of the cases. Among the malignant lesions, urothelial carcinoma was the commonest accounting for 75.9% of the cases with increased prevalence of high grade papillary urothelial carcinoma (74.1%) and invasive papillary urothelial carcinoma accounting for 73.75% of the cases. Conclusions: The present study has stressed the importance of histopathological examination with special emphasis on the study of serial sections and the importance of inclusion of detrusor muscle in the biopsy for accurate grading and staging so as to decrease the morbidity and mortality and initiate the early management of bladder tumours.